Strategi Guru PAI Mengatasi Kesulitan siswa Dalam Membaca Al-Qur’an Melalui metode pembiasaan di SMK Al Kholily Mlokorejo Puger Jember Tahun Pelajaran 2018/2019 - Badrut Tamami (Universitas Muhammadiyah Jember, 2020)
Education is an important factor which cannot be segregated from the life of all human beings, both individually and collectively. Strategies employed by the teacher of PAI (Islamic education) thus have an important role in establishing students’ personality, especially with regard to their religious character. The teaching of PAI therefore must be performed gradually and continuously. Students' ability in reading Qur'an must be improved significantly. A method of habituation constitutes one that can be used to improve students' ability in reading Qur’an. The problems in this research are as follows: 1. How did a PAI teacher overcome problems and difficulties in reading Qur'an through the use of a habituation method at SMK Al Kholily Mlokorejo Puger Jember?; 2. What were inhibiting factors and what were the solutions? This study employed a qualitative approach in the form of a case study. Data were colleted by ways of observation and interviews. The respondents were students at SMK Al Kholily Mlokorejo Puger Jember. The results revealed that the difficulties in reading Qur’an can be improved through the use of a habituation method.